Complex Fracture Closure Pressure Analysis During Shut-in: A Numerical Study. Issue 4 (July 2022) - Wang, Daobing; Ge, Hongkui; Wang, Xiaoqiong; Wang, Yang; Sun, Dongliang; Yu, Bo
Conventional fracture closure models typically assume homogeneous formation. This assumption renders complex fracture closure pressure analysis during shut-in insufficient at present. In this paper, we use a cohesive zone method (CZM)-based finite element model to obtain the fracture closure pressure and minimum horizontal principal stress of the major fracture and the branch fracture based on pressure fall-off analysis. Key factors including leak-off rate, injection time, and stress anisotropy are discussed in detail. A quantitative relationship between fracture closure pressure and these factors is plotted to reduce or eliminate the errors caused by conventional fracture injection diagnostic models. The results show that leak-off rate, injection time, and stress anisotropy have a significant effect on the fracture closure process. Fracture closure in naturally fractured formations is a slow process, and the early closure pressure represents the closure of the branch fracture, which is much higher than the minimum horizontal stress. This investigation provides new insight into how to estimate the in-situ stress in naturally fractured reservoirs.